Rule of law and justice system in Latin America - Pásara Pazos, Luis (2007)
This article explores the conditions offered by the justice system in Latin America to effectively accomplish the Rule of Law. Firstly, it reviews the heritage of the legal tradition in the region, in which the notion of Rule of Law is absent and judges did not practice constitutional and legal review. Justice reform is characterized, to some extent, as an alien project looking for better conditions for a market system in the context of State reform. Its achievements and shortcomings are appraised, and legal pluralism proposals are discussed. Finally, by recognizing the existence of «low intensity citizens» in Latin America the author rejects the idea of making a revolution through justice reform and proposes to constraint the latter to a set of feasible objectives for benefiting the average citizen.